Use of the online catalogue of the National University's documentary information system by users of the Biblioteca "Joaquín García Monge": Level of knowledge - Fallas Ceciliano, Shirley (2004)
What level of knowledge and success in locating information have users of the Library "Joaquín García Monge" in using the online catalog Documentary Information System of the National University (SIDUNA), Heredia, Costa Rica?.